Evaluation of a new packaging process for non-autoclavable endoscopes: results for the first 100 microbiological samples. Issue 4 (December 2017) - Minebois, C.; Saviuc, P.; Shum, J.; Tuvignon, P.; Pelloux, I.; Brenier-Pinchart, M.-P.; Landelle, C.; Mallaret, M.-R.
Summary: Background: A new process for packaging endoscopes (SureStore ®, Medical Innovations Group) immediately after they exit from washing and disinfection in an automated endoscope reprocessor (AER) allows for endoscopes to be stored for up to 15 days. Aim: To describe the microbiological quality of samples from gastrointestinal endoscopes following this process. Methods: Three-month prospective study using microbiological sampling from a stock of 38 gastrointestinal endoscopes carried out in a French University Hospital. The compliance rate (proportion of samples ≤25 cfu with no pathogenic micro-organisms) and the rate of sterile samples (proportion of germ-free samples) were calculated. We then used multivariate analysis to determine the factors associated with the maintenance of sterility. Findings: One hundred samples were taken from stored endoscopes: 31 stored for ≤3 days, 34 stored between 3 and 7 days, and 35 after storage between 7 and 15 days. The compliance rate was 98% and the sterile sample rate was 60%. Only the time between leaving the AER and packaging was significantly associated with the sterility of samples ( P  = 0.02). The probability of having a sterile sample decreased 17-fold when the endoscope was packaged >2 h after leaving the AER ( P  = 0.04) compared to an endoscope packaged within 1 h after leaving the AER. Conclusion: The SureStore process seems capable of satisfactorily maintaining compliance (98%) of samples taken from endoscopes stored for up to 15 days. The delay in packaging should not exceed 1 h, as the rate of sterile samples decreases thereafter.